La mimesis aristotélica más allá de los límites de la Poética - Suñol, Viviana (2005)
From Renaissance on, Aristotelian mimesis had exerted its influence mainly through the principie that "art imitates nature". This principie was interpreted in different and multiple ways reaching its most categorical rejection with nineteenth-century aestheticism. What is surprising is that this principie was neve r explicitly enunciated in the Poetics as subject of the téchne poietiké, although it is frequently mentioned in different treatises devoted to the study of natural history, e.g. Meteor., Phys., Protr., etc. 1n the first pari of this paper, I present a brief examination of some passages that I believe gives evidence of the analogical value that mimetic vocabulary usually has in Aristotle. Then, in the second part I analyze the different formulations of the principie in the corpus in order to elucidate the complex relation of analogy and supplementation between the sphere of art and that of nature. My attempt contradicts Halliwell's interpretation (1999 & 2002), to whom it is imperative to distinguish the wider uses of the term from the proper artistic signification of mimesis in Aristotle's Poetics